Effect of trace metals on reactive crystallization of gypsum - SAYAN, PERVİZ; SARGUT, SİBEL (WILEY-V C H VERLAG GMBH, 2007)
The effect of Fe2+, Fe3+, and Cr3+ ions on crystallization of calcium sulfate dihydrate (gypsum) produced by the reaction between calcium hydroxide suspension and sulphuric acid solution was investigated at 3.5 pH and 65 degrees C in the absence and presence of 2500 ppm citric acid concentration. Crystal size distributions, filtration rates, and morphology of gypsum were determined and discussed as a function of ion concentration. Average particle size of gypsum was not affected significantly by the presence of Fe2+, Fe3+, and Cr3+ ions individually. Variation of gypsum morphology depending on ion concentration affected the filtration characteristics. The presence of Fe3+ or Cr3+ ions besides 2500 ppm citric acid influenced both average particle size and filtration characteristics. The effect of citric acid on gypsum morphology was suppressed at high Fe3+ and Cr3+ ion concentrations. The change of morphology is related to the complex formation between Fe3+ or Cr3+ ions and citric acid at high ion concentrations. (c) 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: calcium sulfate dihydrate; gypsum; trace metals; citric acid; crystal size distribution; CALCIUM-SULFATE DIHYDRATE; PHOSPHORIC-ACID PRODUCTION; SIMULATED CONDITIONS; GROWTH; ADDITIVES; CRYSTAL